Engagement among Selangor State Development Corporation (PKNS) employees / Siti Sajarotun Nur Baharuddin - Baharuddin, Siti Sajarotun Nur (Faculty of Business and Management, 2020)
Due to the challenging economic climate, many organizations deciding to restructure and resize for the survival in the marketplace which resulted organizations constantly seek for different methods to keep their employees engaged. Hence, employee engagement can be defining as employee that physically and emotionally show full commitment towards their job to achieve the goals of organization. Therefore, the purpose of this research is to investigate the factors influencing the employee engagement at Selangor State Development Corporation. This study used simple random sampling techniques and self-administrated questionnaire as an instrument to collect data. The data from 100% out of 278 employees are collected then evaluated by using statistical package for the Social Science (SPSS) version 23 software. The result from Multiple Regression analysis indicates that all the elements in predict employee engagement which is leadership, working environment and organizational culture have positive and significant relationship with employee engagement. Moreover, working environment found to be the most influential variables towards employee engagement at Selangor State Development Corporation.